Seed briquette composition for the direct seeding of Gmelina Gmelina arborea Roxb. - Andreas Therapy; Dolly Priatna; Dede Jajat Sudrajat (Indonesian Journal of Applied Environmental Studies, 2020)
The study of the effect of briquette composition on the seedling survival and growth of Gmelina in the field with the Randomized Group Design (RGD) experimental method. The parameters observed in the seed briquette composition test in the field were seedling diameter, seedling height and life percentage. The data were analyzed by Analysis of Variance (ANOVA) and Duncan's Test using SAS and SPSS programmes to determine the success of the seed briquette composition test. The composition of seed briquette has a significant effect on the survival percentage and growth of direct seeding Gmelina in the field. The application of the composition of B-5 with land preparation in the form of cleaning gives the best percentage of life and growth of Gmelina seedlings. This composition also gave a high growth of 45.29 cm, a diameter of 5.16 cm and a percentage of life of 58.33%. The composition of the B-5 seed briquettes has a proportional composition of the main ingredients in the form of soil and compost which is 20% and 40% as a growing medium and a source of nutrition for Gmelina seedling growth.Penelitian  tentang  pengaruh  komposisi briket terhadap  persen hidup serta  pertumbuhan  Gmelina  di lapangan  dengan  metode eksperimen Rancangan  Acak Kelompok (RAK). Parameter yang diamati pada uji komposisi briket benih di lapangan adalah diameter semai, tinggi semai dan persentase hidup. Data dianalisis dengan Analisis Ragam dan Uji Duncan dengan menggunakan program SAS dan SPSS untuk mengetahui  keberhasilan dari uji komposisi briket benih. Komposisi briket benih berpengaruh  nyata  terhadap persentase hidup dan pertumbuhan direct  seeding  Gmelina di lapangan.  Penerapan komposisi B-5 dengan persiapan lahan berupa pembersihan memberikan persentase hidup dan pertumbuhan semai Gmelina terbaik. Komposisi ini juga memberikan pertumbuhan tinggi sebesar 45,29 cm, diameter sebesar 5,16 cm dan persen hidup sebesar 58,33%. Komposisi briket benih B-5 memiliki komposisi bahan utama berupa tanah dan kompos yang proporsional yaitu sebesar 20% dan 40% sebagai media tanam dan sumber nutrisi untuk pertumbuhan semai Gmelina.